Response to letter for critiques on our published article: Effect of tracheal tube cuff inflation with alkalinized lidocaine versus air on hemodynamic responses during extubation and post-operative airway morbidities in children: prospective observational cohort study, Ethiopia - Biniam Assefa; Hirbo Samuel; Fissiha Fentie; Tenbite Daniel; Assefa Hika; Bacha Aberra; Belete Alemu (BMC Anesthesiology, 2023)
Abstract Endotracheal tube with an inflated cuff was used to manage and maintain the airway during general anesthesia in children. When the lateral pressure exerted by an inflated Endotracheal tube cuff on tracheal mucosa exceeds capillary perfusion pressure, patients may complain of cough, sore throat, and hoarseness in the postoperative period.